A tornado in the family: fetal alcohol spectrum disorder and aggression during childhood and adolescence: a scoping review - Champagne, Maude; McCrossin, Jeffrey; Pei, Jacqueline; Reynolds, James N. (Frontiers in Neuroscience, 2023)
Background Aggression exhibited by children and youth with Fetal Alcohol Spectrum Disorder (FASD) toward family members is a major cause of stress and anxiety for caregivers, but relatively little attention has been directed toward designing interventions specific to this phenomenon. In light of the serious negative impact of this issue for families, a scoping review was undertaken to summarize the evidence available on psychosocial interventions that may mitigate the frequency and severity of aggression exhibited by children and youth with FASD toward family members. Methods This review was designed using PRISMA-SCR and JBI scoping review guidelines. Three databases were searched in August 2021: EMBASE, PsychINFO, and Medline. Results A total of 1,061 studies were imported for screening with only five studies meeting full eligibility criteria. None of the interventions were aimed at specifically targeting aggression and instead reported on broader constructs of externalizing behaviors such as hyperactivity. The interventions were limited to school-aged children. Studies reported primarily on child outcomes while only one reported on family related outcomes. Conclusion Following from this review of the literature, we argue that aggression is a related but separate construct from other behavioral problems most frequently targeted by parenting interventions. Given the often dire consequence of aggression displayed by children and youth with FASD and the limited number of studies, there is an urgent need for research on how to support families to manage this specific type of behavior in this population.